PENGARUH PROMOSI PENJUALAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN ACE HARDWARE GRAND INDONESIA - Siti Aprilliani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of sales promotion and service quality on purchasing decisions of ACE Hardware Grand Indonesia consumers. The research method uses quantitative. The population in this study were consumers who had shopped at ACE Hardware Grand Indonesia, while the number of samples used was 122 respondents. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results showed that: (1) Partially there is a positive and significant influence between sales promotions on purchasing decisions, with the regression equation Y = 4.675 + 0.912X?, and the coefficient of determination is 62%. (2) Partially there is a positive and significant effect between service quality on purchasing decisions, with the regression equation Y = 5.583 + 0.423X?, and the coefficient of determination is 57.7%. (3) Simultaneously, there is a positive and significant effect of sales promotion and service quality on purchasing decisions of ACE Hardware Grand Indonesia consumers, with the regression equation Y = 1.508 + 0.586(X?) + 0.236(X?), and the coefficient of determination is 72, 1%.